STANDAR PELAYANAN PERIZINAN PENDIRIAN ATAU OPERASIONAL PENDIDIKAN FORMAL MAUPUN NON FORMAL BERBASIS DIGITAL DI DINAS PENDIDIKAN KOTA SURABAYA - Romdhonie, Muhammad Dikry; Oktariyanda, Trenda (Publika, 2023)
Licensing services for the establishment or operation of formal and non-formal education are a form of government effort in meeting community needs in the education sector. The implementation of public services has benchmarks in what are called public service standards. This study aims to describe service standards for the establishment or operation of digital-based formal and non-formal education permits at the Surabaya City Education Office. This type of research is descriptive qualitative approach. This study focuses on public service standards based on Permenpan-RB Number 15 of 2014 concerning Service Standard Guidelines which include: requirements, procedures, time, costs, products, complaint management. Licensing services are quite good but not optimal. In terms of the legal basis for determining clear requirements coupled with socialization from the Education Office and the community. the procedure has deficiencies in efficiency and effectiveness as well as the process of returning the wrong application file. fast service time, but less than optimal if there is an incorrect application file. Then free service fees in accordance with applicable regulations and the announcement of free fees at the Office of Education. the service product is in the form of a soft file in the form of a decision letter from the head of the service which is the basis for issuing a permit. Responsive and solutive complaint management is accompanied by the availability of facilities to accommodate complaints, namely in the Office or social media, but is not optimal in recording complaints that have not been digitized and classified.